Women in the social debate about the marriages in 18Th-Century Spain (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
One of the most significant controversy of the many that flourished in the eighteenth century Spanish society revolved around the discredit of the institution of marriage, to the decline in the number of marriages and the high rate of marital failure controversial. Given the magnitude of the problem, it involved people of all types and condition would; from theologians and moralists to state servants, judges, writers and politicians, leading to acquire unprecedented spread through the literary and journalistic projection that accompanied it. The multiple aspects dealt resulted in a rich debate which would be put into question, inter alia, the role played by women, which is just blaming the problem. From the perspective of gender this paper analyzes the key factors that put women at theepi center of the debate to press and counter models and counter models female supported by the liberal ideology, in keeping with the renewal of the domestic woman archetype.
Keywords: Social controversy; discredit marriage; guilty women; models and counntermodels female; domestic woman archetype.